Ground-state structures, physical properties and phase diagram of carbon-rich nitride C5N. (31st August 2018) - Wu, Qinghua; Hu, Qianku; Hou, Yiming; Wang, Haiyan; Zhou, Aiguo; Wang, Libo
Abstract: Using the ab initio evolutionary algorithm, four thermodynamically stable C5 N phases (, -1, -2 and C2/m ) are uncovered. The structures of the, -1 and -2 phases possess layered features. The dense C2/m phase with 3D strong covalent bond network is calculated to be superhard with hardness of 75.4 and 83.9 GPa by Chen and Gao models. The electronic properties of the C5 N is diverse including conductor ( ), indirect semiconductor ( -1 and -2) and direct semiconductor ( C2/m ). Pressure-induced phase transition sequences and critical pressure points are calculated to be → -1 → -2 at 2.7 and 34 GPa, respectively. Though the C2/m phase is metastable at zero temperature, our established pressure-temperature phase diagram of C5 N shows that the C2/m becomes stable under high temperatures and pressures. The pressure-temperature phase diagram will give theoretical guidance for further experimental synthesis of different C5 N phases.